PENGARUH PERSEPSI EKOWISATA TERHADAP TINGKAT KEPUASAN WISATAWAN DI MONKEY FOREST UBUD, BALI - Reza Efrida, Via; Sudiarta, I Nyoman; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017)DO - 10.24843/IPTA.2017.v05.i01.p11, 2017)
This study aims to investigate (1) the ecotourism perception of tourists visiting Monkey Forest Ubud; (2) the visitor satisfaction level on Monkey Forest Ubud attraction; and (3) the influence of ecotourism perception on visitor satisfaction level at Monkey Forest Ubud. The result of this research carried out descriptive statistic by using an importance-performance analysis (IPA) and inferential statistic by using a simple linear regression analysis. The technique of determining sample size is incidental sampling technique by distributing questionnaires to 170 tourists visiting Monkey Forest Ubud. The result showed that tourists which visit Monkey Forest Ubud strongly agree on the implementation of ecotourism concept. On the other hand, the calculation results of concordance rate showed 89.59% which means that the overall tourist is satisfied with the Monkey Forest Ubud attraction. Moreover, based on the hypothesis testing by using t-test statistical significance showed that there is a significant influence of independent variable (perception of ecotourism) on the dependent variable (tourist satisfaction).
Keywords: Perception of Ecotourism, Tourist Satisfaction